Multidisciplinary Approach to the Perinatal Care of Families Affected by Fetal Anomalies [25G]. Issue 1 (May 2017) - Kodeih, Hanna; Maher, James; Schlabritz-Lutsevich, Natalia; Angelis, Dimitrios; Kelly, Randall; Hampton, Moss
Abstract : INTRODUCTION: The prenatal diagnosis of a congenital anomaly occurs in 2-3% of all pregnancies and affects 120, 000 births annually. Ultrasonographic diagnosis has dramatically changed the neonatal care of affected infants, allowing for effective matching of the delivery site with the neonate's post-delivery needs, when instability is anticipated. We believe our perinatal conference improves neonatal outcomes, resource utilization, and patient satisfaction. Additionally, this conference offers coordination of care essential for optimal delivery planning, patient education, and neonatal consultation. We would like to study these parameters. METHODS: At Texas Tech University Health Sciences Center School of Medicine Permian Basin Obstetrics and Gynecology Department, perinatal conference is a multidisciplinary conference which is used as a tool for: 1) Dissemination of information about complex problems to the health care team 2) Discussion of core needs and delivery plans, 3) Education in ultrasound for residents and faculty in families affected by fetal anomalies. This conference includes review of antenatal patients with fetal anomalies, followed by review of ultrasound images and discussion of care plan. Fetuses with structural problems often require delivery at a surgical center. This conference aids in avoiding inappropriate local deliveries, emergent delivery, and neonatal transport. This conference serves to facilitate communication on status of affected pregnancies, updates of delivered babies, and quality improvement opportunities for future infants. RESULTS: Retrospective analysis has shown fewer inappropriate deliveries and associated decrease in utilization of resources. CONCLUSION: Prenatal ultrasound diagnosis of congenital anomalies in combination with multidisciplinary management provides a critical opportunity to improve patients' care and physician education.